RELATIONSHIP BETWEEN HEALTH BEHAVIOR AND THE EVENT OF DENGUE HEAVENLY FEVER (DHF) - Revelation Mahardika (Sean Institute, 2021)
The incidence of Dengue Hemorrhagic Fever (DHF) in the working area of ​​the Cepiring Health Center in 2008 was recorded as 91 cases with 2 deaths. The purpose of this study was to determine what health behaviors were associated with the occurrence of Dengue Hemorrhagic Fever (DHF) in the working area of ​​the Cepiring Health Center. This type of research is an analytical survey research using a case-control approach. The instruments used in this study were 1) questionnaires, 2) data on patients with dengue fever at the Cepiring Health Center and DKK Kendal. From the results of the study, it was found that the significant factors were: cleaning water reservoirs (p value = 0.044, OR = 2.513), closing water reservoirs (p value = 0.002, OR = 4,333), draining water reservoirs (p value = 0.004, OR=3.857), burying used goods (p value=0.014, OR=3.095),